A questão religiosa, a escola e a cultura de paz - Alves, Gizele Evangelista de Oliveira (2019)
The objective in this research, titled The religious question, Education and Culture of Peace, aims to check out how the education scope face the religion in the contemporary society and how the religion issue contribute for understanding and potentiation culture of peace. We will discuss the concept of religion and free religious, focused on the fundamental right of free choice, exercise and manifestation religious that permit each person the individual or collective exercise of their faith. As a social life space, we will also analyze if/and the school guarantee the safe religious manifestation of their participants. Therefore, this research anchored itself in the justification of the liberties fundamental right, among them, the religious, as demonstration of guarantee of democracy in all spaces, defending pluralism, the diversity, the multiculturalism and laic education. As a methodological procedure of this research, we will take on board of theoretical-bibliographical perspective, as main source and theoretical references the works by Max Weber, Leonardo Boff, Jürgen Habermas, Luiz Antônio Cunha and Dalai Lama.